'Give-up-itis' revisited: Neuropathology of extremis. (November 2018) - Leach, John
Abstract: The term 'give-up-itis' describes people who respond to traumatic stress by developing extreme apathy, give up hope, relinquish the will to live and die, despite no obvious organic cause. This paper discusses the nature of give-up-itis, with progressive demotivation and executive dysfunction that have clinical analogues suggesting frontal-subcortical circuit dysfunction particularly within the dorsolateral prefrontal and anterior cingulate circuits. It is hypothesised that progressive give-up-itis is consequent upon dopamine disequilibrium in these circuits, and a general theory for the cause and progression of give-up-itis is presented in which it is proposed that give-up-itis is the clinical expression of mental defeat; in particular, it is a pathology of a normal, passive coping response.